ANALISIS PESAN DAKWAH SYAFIQ RIZA BASALAMAH DI MEDIA SOSIAL INSTAGRAM - Alfatih Yusry S.; Nursapia Harahap; Syahrul Abidil (Lafadz Jaya Publisher, 2023)
This study aims to analyze the contents of the indictment message on the Instagram account @syafiqrizabasalamah_official and the use of Instagram media as a da'wah media. This study uses a descriptive qualitative research method. The theory used in this research is the theory of the message of Jalaluddin Rakhmat's message. Data collection techniques are carried out by observation and documentation. The results of this study indicate that there are 15 da'wah posts for the period 1-26 September 2022 which the researchers have analyzed. Of these, it was found that there were 5 posts of aqidah preaching, 5 posts of moral preaching and 5 posts of sharia preaching. Researchers also consider that Instagram is quite effective as a medium for preaching, especially for those who cannot attend science assemblies.